PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF T-SUR BERBASIS CONSTRUCT 2 PADA MATERI SISTEM TATA SURYA UNTUK SISWA KELAS VI SD NEGERI BURENGAN 1 - Fransisca Tantivanelya Yonatan; Bagus Amirul Mukmin; Kukuh Andri Aka (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT This study was motivated by the limited use of instructional media in teaching the Solar System topic to sixth-grade students at SD Negeri Burengan 1, which resulted in difficulties in understanding the learning material. The purpose of this study was to develop the T-SUR interactive learning media based on Construct 2 and to determine its validity, practicality, and effectiveness. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included a material expert, a media expert, a sixth-grade teacher, and sixth-grade students at SD Negeri Burengan 1. Data were collected through observations, interviews, questionnaires, and tests. The data were analyzed using descriptive quantitative analysis by calculating the percentages of validation results, user responses, and students' learning outcomes. The findings indicated that the T-SUR interactive learning media based on Construct 2 was feasible for use in teaching the Solar System topic in elementary school science and social studies (Ilmu Pengetahuan Alam dan Sosial [IPAS]). The media met the criteria of validity, practicality, and effectiveness based on the results of the field trials. The implementation of the T-SUR media enhanced students' conceptual understanding, classroom engagement, and learning interest, making it a viable alternative for innovative instruction in elementary school IPAS. Therefore, the T-SUR interactive learning media developed using Construct 2 can serve as an innovative and effective instructional medium to support the teaching and learning process in elementary schools. ABSTRAK             Penelitian ini dilatarbelakangi oleh rendahnya penggunaan media pembelajaran pada materi sistem tata surya di kelas VI SD Negeri Burengan 1 yang menyebabkan peserta didik mengalami kesulitan dalam memahami materi sistem tata surya. Tujuan penelitian ini adalah untuk mengembangkan media pembelajaran interaktif T-SUR berbasis Construct 2 serta mengetahui tingkat kevalidan, kepraktisan, dan keefektifannya. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE yang meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Subjek penelitian terdiri atas ahli materi, ahli media, guru kelas VI, dan peserta didik kelas VI SD Negeri Burengan 1. Teknik pengumpulan data menggunakan observasi, wawancara, angket, dan tes. Data dianalisis menggunakan teknik analisis deskriptif kuantitatif dengan menghitung persentase hasil validasi, respon pengguna, dan hasil belajar peserta didik. Hasil penelitian menunjukkan bahwa media pembelajaran interaktif T-SUR berbasis Construct 2 dinyatakan layak digunakan dalam pembelajaran IPAS materi sistem tata surya. Media ini memenuhi aspek kevalidan, kepraktisan, dan keefektifan berdasarkan hasil uji coba yang dilakukan. Penerapan media T-SUR berbasis Construct 2 mampu mendukung peningkatan pemahaman, keaktifan, dan minat belajar siswa, sehingga dapat menjadi alternatif media pembelajaran inovatif untuk pembelajaran IPAS di sekolah dasar. Dengan demikian, media pembelajaran interaktif T-SUR berbasis Construct 2 dapat dijadikan sebagai alternatif media pembelajaran yang inovatif dan efektif untuk mendukung proses pembelajaran di sekolah dasar.